Vertical externalities with lump-sum taxes: how much difference does unemployment make? - Diego Martinez-Lopez; Tomas Sjongren (European Journal of Government and Economics (EJGE), 2014)
This paper analyses how the existence of unemployment affects the conventional approach to vertical externalities. We discuss the optimality rule for the provision of public inputs both in a unitary and in a federal state. Our findings indicate that decentralising spending responsability on public inputs in the presence of unemployment allows output to be closer to the first best level. Moreover, we describe the inability of the federal government, behaving as a Stackelberg leader, to replicate the unitary outcome, unless there are new policy instruments at government's disposal.
Keywords: 330; Public inputs; unemployment; vertical externalities